A mapping survey of digital clinical consultations in maternity care in England. - Georgia Clancy; Kerry Evans; Helen Spiby; Victoria Barrett; Candice Sunney; Catrin Evans (PLOS Digital Health, 2025)
Many areas of healthcare are exploring the use of digital technologies with the aim of improving and expanding care to service users. In England, maternity care is currently undergoing a digital transformation in line with the National Health Service's (NHS) Long Term Plan, which seeks to enhance care delivery and accessibility through digital tools. However, there is a lack of data on the current use and practice of digital consultations across the country. This project aimed to map and explore how digital clinical consultations are currently being used by NHS maternity care services in England. An online survey was designed to capture data on current practice, guidance and procedures to address potential inequalities. The survey was distributed to each NHS Trust (n = 121) that provides maternity care (specifically to senior maternity care professionals and digital maternity leaders who could provide an overview of how digital consultations were being used where they worked). The survey was open between January and March 2024. 53 completed surveys were received representing 39 different organisations (32% of those currently providing maternity care in England). Quantitative summary statistics indicated that telephone consultations were the most commonly used digital modality across all stages of the maternity care pathway. Thematic analysis identified barriers such as a lack of staff consultation and lack of staff training on the use of digital consultations. It was uncommon for women to be asked about their consultation preferences or assessed for individual needs. In conclusion, the findings reveal significant variation in the use of digital consultations, highlighting a gap between policy intentions and practice. Key areas for improvement in the delivery and implementation of digital consultations include staff training, systems to record women's consultation preferences/needs, and more research to support digital inclusion. The findings of this survey have the potential to have applications beyond maternity care and in different geographical contexts.